Resilience to depression and unchanged quality of life in Sardinian old adults during COVID-19 lockdown - Cossu, Giulia; Atzeni, Michela; Cantone, Elisa; Forte, Viviana; Tusconi, Massimo; Kalcev, Goce; Maleci, Alberto; Montisci, Roberta; Ferreli, Caterina; Atzori, Laura; Primavera, Diego; Dursun, Serdar M; et al. (Frontiers in Psychiatry, 2025)
IntroductionOlder adults were expected to be particularly vulnerable to depressive symptoms during the COVID-19 lockdown due to social isolation, disruption of daily rhythms, and higher mortality risk. However, some studies have reported unexpected resilience in this population. This study aimed to assess resilience, operationalized as stability in depressive symptoms and health-related quality of life (H-QoL), before and during lockdown among older adults in Sardinia, Italy.MethodsWe conducted a cohort follow-up study including community-dwelling older adults aged ≥65 years, originally enrolled in a randomized controlled trial promoting active aging. Participants were assessed at baseline (March-April 2019) and during lockdown (March-April 2020) using the Patient Health Questionnaire-9 (PHQ-9) and the Short-Form Health Survey (SF-12). Three groups were analyzed: 1. Study cohort, same participants assessed before and during lockdown (pre-post comparison). 2. National matched sample, extracted from a large Italian epidemiological survey, matched by age and sex, for comparison of SF-12 scores. 3. Regional matched sample, extracted from a Sardinian epidemiological survey, matched by age and sex, for comparison of PHQ-9 prevalence rates. Statistical analyses included ANOVA for continuous variables and Chi-square tests for proportions.ResultsNinety-three older adults (mean age 73.4 ± 5 years; 53.8% female) were included in the study cohort. No significant differences were found in SF-12 scores between baseline and lockdown (35.7 ± 4.5 vs. 34.3 ± 6.4; F (1,84) = 2.999, p = 0.085) or in PHQ-9 scores (2.3 ± 3.0 vs. 2.3 ± 3.5; F (1,84) = 0.035, p = 0.851). The proportion of participants with moderate/severe depressive symptoms (PHQ-9 ≥10) showed a non-significant increase (3.2% vs. 6.5%; p = 0.305). Comparisons with the national and regional matched samples also revealed no statistically significant differences.DiscussionOlder adults in Sardinia demonstrated resilience during lockdown, maintaining stable levels of depressive symptoms and quality of life. Potential protective factors include strong family networks, maintenance of daily rhythms, and limited digital overexposure. These findings align with reports from other Western countries and warrant further research into cultural and social determinants of resilience in aging populations during crises.Clinical trial numberNCT03858114.